SCREENING OF PESTICIDE DEGRADING AND BIOSURFACTANT PRODUCING BACTERIA FROM CHLORPYRIFOS CONTAMINATED SOIL - KAVITHA D,; SURESHKUMAR M,; SENTHILKUMAR B, (International Journal of Pharma and Bio Sciences, 2016)
Pesticides have played a significant role in food production, and in view of growing worldwide food demand. This has resulted in serious concern about environmental contamination. Many remediation technologies are used to remove the pesticides from the soil. The use of biosurfactant enhanced bioremediation of pesticides. Biosurfactants are valuable surface active molecules produced by wide variety of microorganisms. Due to its amphipathic nature, these biomolecules are capable of lowering the surface tension, interfacial tension and forming micro emulsion to enable mixing of two immiscible solutions. Such properties exhibit excellent detergency, emulsifying, foaming, and dispersing traits. Some of the features, which make them promising alternatives to chemically synthesized surfactants, are their lower toxicity, higher biodegradability, greater stability at wide range of pH and temperature, and better environmental compatibility. This research was conducted to investigate the chlorpyrifos degrading bacteria and the bacteria having the ability to produce surfactants (biosurfactants) isolated from the pesticide-contaminated soil. The isolate (MCAS01) was identified as Pseudomonas stutzeri by comparing its 16S rRNA sequence with those available in The National Centre for Biotechnology Information (NCBI) gene bank. The strain was selected for its ability to produce extra cellular products (biosurfactants) able to reduce surface tension. The objective of this study was to isolate and characterize the surface active components from the crude biosurfactant produced by Pseudomonas stutzeri MCAS01. To confirm the ability of this isolate in biosurfactant production, different screening methods including blood hemolysis, emulsification, methylene blue reduction assay, drop-collapse, Cetyl Tri Ammonium Bromide (CTAB) and determination of surface tension were assessed. The fraction rich in glycolipids was obtained by the fractionation of crude biosurfactant using acid precipitation method and further identified using Thin Layer Chromatography and FT-IR. FT-IR results confirmed it to be glycolipid type of biosurfactant. It showed stability on exposure to high temperature (up to 100oC), the surface tension was reduced up to 30mN/m as well as the emulsification index E24 was 65%. Properties of the biosurfactant that was separated by acid precipitation were investigated. The biosurfactant activity was stable at high temperature with wide range of pH and salt concentrations. Thus the biosurfactant are required to make the field application competitive with chemical surfactants.